2013
DOI: 10.1016/j.jegh.2012.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pulmonary tuberculosis among expatriates subjected to medical visa screening in Abu Dhabi, United Arab Emirates

Abstract: The number of active PTB cases among applicants for visa screening is still of a real concern. Without a rigorous screening system, the disease can spread to the community and hit other people. Certain subgroups were more likely to have the disease; this could provide the scientific foundation for future amendments in the screening requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…Despite high trafficking of tuberculosis (TB) in UAE [ 16 ], the prevalence of latent TB infection (LTBI) in the Emirate of Abu Dhabi among pediatric patients presenting for routine care is relatively low (0.45%) [ 17 ]. BCG vaccine may have contributed to this low prevalence in the country, especially since the prevalence of LTBI among Emirati medical students is much higher (8–10%) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite high trafficking of tuberculosis (TB) in UAE [ 16 ], the prevalence of latent TB infection (LTBI) in the Emirate of Abu Dhabi among pediatric patients presenting for routine care is relatively low (0.45%) [ 17 ]. BCG vaccine may have contributed to this low prevalence in the country, especially since the prevalence of LTBI among Emirati medical students is much higher (8–10%) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was further complicated by problems in TB contact tracing due to frequent changes of location and use of bunk-style accommodation among temporary workers [9]. A study from the United Arab Emirates among migrants undergoing medical visa screening found that the TB prevalence among new applicants (first screening) was significantly higher (49.3 per 100 000) than among migrants who underwent repeat screening for visa renewal (25.2 per 100 000) [99]. Travel back to the country of origin was, however, not captured in the study and it is therefore not possible to determine whether the risk of TB decreased significantly despite return visits to the home country.…”
Section: Short-term Visitors and Those With Long-duration Multiple-enmentioning
confidence: 99%
“…Tuberculosis is a global public health problem. The results of the Al Hosani's study confirm this aspect: the prevalence of active TB between expatriate adult expatriates in the United Arab Emirates (about 39 per 100,000) is about 14 times higher than the estimated prevalence of tuberculosis in the native population [21]. According to the study by Gao and colleagues, China and in particular the Sichuan Province is one of the countries with the highest prevalence of tuberculosis, settling on 459 cases out of 100,000.…”
Section: Infectious Diseasesmentioning
confidence: 73%